Shariah Supervisory Board and Islamic Banks’ Financial Performance: An Evidence from Southeast Asia - Abdul Hamid; Khairatun Hisan; Khairul Anuar bin Ahmad (IAIN Langsa, 2023)
This study aims to find out the effect of SSB Characteristics on financial performance of Islamic Banks in Southeast Asia, particularly in Malaysia and Indonesia. To establish the relationship between SSB characteristics and financial performance, secondary data from banks’ annual report was collected and then analysed using Panel data regression model and T test with the help of Eviews 10.Result shows that there is no significant effect of the observed characteristics (size, doctoral degree, number of meetings) on financial performance of Islamic banks Originality/value – the strength of this study is that it focuses on the two most prominent countries regarding Islamic finance in Southeast Asia.